Multiple domain-general assessments of cognitive functions in elite athletes: Contrasting evidence for the influence of expertise, sport type and sex - Vona, M.; de Guise, É.; Leclerc, S.; Deslauriers, J.; Romeas, T. (Psychology of Sport and Exercise, 2024)
Converging evidence has shown that domain-general cognitive abilities, especially executive functions (EF), tend to be superior in sport experts. However, recent studies have questioned this cognitive advantage and found inconsistent findings when comparing sport type and sex. This study aimed to compare the impact of sport expertise, sport type, and sex on various domains of cognitive functions.